Tectonic controls on residual oil saturation below the present-day fluid contact level in reservoirs of the Persian Gulf. (1st April 2020) - Heydari-Farsani, E.; Neilson, J.E.; Alsop, G.I.; Hamidi, H.
Graphical abstract: Presence of residual oil below the present-day FWL is related to the north-east downward tilting of the entire Persian Gulf foreland basin. Highlights: Residual oil occurs below the current fluid contact in many Middle Eastern reservoirs. This is related to tilting of the Arabian Plate towards the Zagros mountains. Tilting changed the equilibrium of the reservoirs and their fluid contents. Water partly replaced oil at the base of reservoirs creating residual oil zones. Abstract: The presence of residual oil below the present-day free water level (FWL) and oil water contact (OWC) is common in many oil fields in the Middle East, particularly those in the Persian Gulf. This residual oil is seen in both clastic and carbonate reservoirs prior to the start of production. The characterisation and modelling of these fields is difficult in practice. Also, these residual oils below the FWL and OWC could become classified as reserves if ways to produce them could be found. However, the first step is to better understand their origin. Therefore, the goal of this study was to investigate the role of geological events on the presence of the residual oil zone (ROZ) below the FWL and OWC. It has been suggested that the presence of residual oil below the present day FWL and OWC is related to the geotectonic history of the region. From the middle Miocene, reverse faulting and overfolding propagated over the Zagros, leading to the amplification of folds and the migration of the Zagros orogeny towards its foreland basin (Persian Gulf). In response to this additional massive loading on the continental margin, the forebulge amplitude was increased, its location migrated towards the uplifted Zagros Mountains, and consequently the Persian Gulf became narrower. This exerted a north to north-east downward tilting of the entire basin, including all the structures and reservoirs previously filled by hydrocarbons. This basin tilting changed the equilibrium of the structures and their fluid contents, and resulted in the hydrocarbons and water attempting to find a new equilibrium. Under these conditions, the early migrated and accumulated oil was flushed out by water (imbibition), and a ROZ was left below the present day FWL and OWCs. The angle of regional basin tilt has been calculated to be 0.836° based on seismic sections.